Church Slavonic legend of St Anastasia according to manuscript Jegor 279 - Čajka, František (Bohemica Olomucensia, 2018)
Church Slavonic legend of St Anastasia is a translation from Latin, made probably in the 10th - 11th century Bohemia. The text of the legend has been preserved in nine manuscripts of Russian origin and a sole manuscript of Serbian origin. The article draws attention to an unknown oldest Russian manuscript Jegor 279 from the second quarter of the fifteenth century. The article contains a basic description of the manuscript, an edition of the text and its textological analysis.
Keywords: Old Church Slavonic; Church Slavonic; manuscript; St Anastasia; St Chrysogonus; textological analysis; edition; hagiography